Effectiveness of Accounting Information Systems and the Affecting Factors - Ni Putu Lisa Ernawatiningsih; Putu Kepramareni (AIBPM Publisher, 2019)
The development of technology in the era of globalization accompanied by the development of technology-based information systems has undergone rapid changes. Accounting information systems are considered an important factor in the sustainability and success of an organization. Accounting information systems can be said to be effective if the system is able to produce information in a timely, accurate and reliable manner. This study aims to obtain empirical evidence of the effects of incentives, level of education, experience and skills on the effectiveness of accounting information systems. The method used in sampling is to use a purposive sampling method with criteria for sampling employees who have implemented a computer-based accounting information system and utilize information technology in carrying out their daily tasks. The data analysis technique used is multiple linear regression analysis techniques. Based on the results of data analysis, it can be concluded that incentives, levels of education, experience, and skills have a positive effect on efektiveness accounting information systems at PT. Angkasa Pura Logistics.